PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS POWERPOINT UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI SIMBIOSIS ANTAR MAHKLUK HIDUP KELAS 3 SD SANTA MARIA PADA TAHUN AJARAN 2024/2025 - Putri; Ita Kurnia; Nurita Primasatya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research and development aims to determine the validity, practicality, andeffectiveness of Powerpoint-based Animated Video Learning Media to ImproveStudent Learning Outcomes on Symbiosis Material Between Living Things inGrade 3 of Santa Maria Elementary School in the 2024/2025 Academic Year. Thisresearch uses Research and Development (R&D) using the ADDIE developmentmodel which consists of five stages, namely analysis, design, development,implementation, evaluation. The subjects of this research are teachers andstudents of grade 3 of Santa Maria Elementary School. The data analysistechniques used are qualitative and quantitative descriptive analysis. The resultsof the research on the development of powerpoint-based animated videos forsymbiosis material in grade 3 of elementary school are (1) The validity test got ascore of 85% from media experts and material experts got a score of 90%. (2) Thepracticality test of teacher and student responses got 89.67% with very practicalcriteria. (3) The effectiveness test of powerpoint-based animated video media canbe seen from the average N-Gain value of 0.8837 which shows very high criteria.It can be concluded that Powerpoint-based Animated Video Learning Media isstated to be very valid, very practical, and very effective for use in learningsymbiosis material.